Consumer protection in an electronic environment - Akhigbe, Iyen Joy (University of South Africa, 2020)
Consumer protection laws have not evolved on par with the development of electronic media. As a result, consumer protection laws do not address all major areas of legal concern that affect the electronic commerce (e-commerce) consumer. Furthermore, differing laws in the area of consumer protection make harmonised consumer protection neigh on impossible. Currently, there is a plethora of laws on the protection of consumers but most of these laws are within the sphere of conventional consumer protection legislation which does not adequately address the legal challenges posed by the proliferation of electronic transactions (e-transactions). Specific e-transaction laws are now to be found in certain international and regional documents emanating from organisations including: the United Nations (UN); the Council of Europe; the Organisation for Economic Cooperation and Development (OECD); the African Union (AU); the Economic Community of West African States (ECOWAS); the Southern African Development Community (SADC); the Common Market for Eastern and Southern Africa (COMESA); and the East African Community (ECA). These legal instruments have already been implemented in certain states’ national legislation, while other countries have yet to accede to them. Despite these legal instruments, e-commerce consumers are faced with inadequate or obsolete legislative provisions and are yet to enjoy full protection equivalent to that accorded to the “traditional” consumer. Furthermore, given the trans-national nature of the internet, divergent laws will inevitably prove to provide inadequate protection to e-commerce consumers. In this research, international and regional legislative instruments, as well as the national laws of selected countries such as the United States (US), the United Kingdom (UK), the Republic of South Africa (South Africa), the Federal Republic of Nigeria (Nigeria), and the Commonwealth of Australia (Australia) are examined. The strengths and gaps in each of these instruments and laws are identified with the aim of harmonising the principles they espouse in a single, cogent, and comprehensive body of rules which could take the form of an international convention. An international convention should be based on national and international best practices. The national adoption of the minimum standards espoused in the proposed Convention will ultimately, promote harmonisation.
Keywords: Borderless jurisdiction; Cooling-off; Cyberspace; E-agent; E-commerce consumer rights; Electronic transferable record; Hidden charges; Information; Keystroke error; M-commerce; Shrinkwrap; Single window facility; Terms and conditions; Transaction; Web-wrap; Wireless Application Protocol